Gender relationship on accepting Reggio Emilia approach in rural early childhood development centres, among parents in Katsina State, Nigeria - Abdullahi, Ibrahim; Zainalaludin, Zumilah (Faculty of Educational Studies, Universiti Putra Malaysia, 2019)
Most rural areas in Africa are confounded with unfavourable gender relationship; strategies are needed, not only being representative but also participatory. This could help in educating the rural populace as the digital society and enhance integrating humanistic and Scientific Values. The study look at gender-based barriers for girl-children manifested more than that of boys due to the training in household chores, instead of schooling. There are many girls-children at school age, but engaged in household chores and street hawking in northern Nigeria. This suggests the need for sensitive gender policy, to focus at local government and rural community levels. In addition, strong advocacy in respect to gender relationship is required with support from religious and community leaders in both the urban and rural areas. The success story of Reggio Emilia Approach in Early Child Development (REA-ECD) acceptance in rural areas of Katsina State Nigeria may be a good motivating factor for governments, NGOs and other development partners to redesign their policies toward this course. To measure the acceptance of the rural populace as parents of digital children in today’s society, Nominal Group Techniques (NGT) was conducted using two groups of twenty parents in each, (males and females) on the acceptance of REA-ECD program. The parents were selected randomly from the register list of the children of the REA-ECD centres. The analysis shows that, issue of female teaches, schools safety and friendly facilities are required to create favourable gender coexisting. The provision of basic facilities in ECD centres safe schools for girls-child and female teachers in rural areas increases gender parity in rural areas. In addition, access to educational opportunities which in long run, will ease rural life and decrease the urban-rural divide and migration. This study is the first of its nature in Katsina State in particular and northern Nigeria at large. The study measured influence of some variables on the acceptance of REA-ECD in rural area of Katsina state. It contributes towards more factors of acceptance in the area of REA-ECD in rural areas of Katsina State, Nigeria.